Nonlinear effects of oil prices on inflation, growth, budget deficit, and unemployment - Nguyen, Thi Ngoc Trang (University of Economics Ho Chi Minh City, 2023)
In oil-exporting countries such as members of the OPEC, fluctua-tions in oil prices exert a significant impact on the domestic econo-my. Currently, a sharp reduction in oil prices results in several ad-verse effects; however, for such a crude-oil exporter that is also an importer of petroleum products as Vietnam, does a rise or drop in oil prices is beneficial to its development? This paper attempts to de-termine the oil price threshold while analyzing oil price effects on several macro factors, such as inflation, GDP growth, budget deficit, and unemployment rate over the 2000–2015 period. Using TVAR model, we detect an oil price threshold of USD27.6/barrel. Moreover, an increase in the price of oil, which exceeds this threshold, will cause a rise in inflation, budget deficit, and unemployment rate. Still, there is no significant evidence of the impact of oil prices on GDP growth.